TCAD simulations of non-irradiated and irradiated low-gain avalanche diodes and comparison with measurements. (1st January 2022) - Croci, T.; Morozzi, A.; Moscatelli, F.; Sola, V.; Borghi, G.; Paternoster, G.; Centis Vignali, M.; Asenov, P.; Passeri, D.
Abstract: In this work, the results of Technology-CAD (TCAD) device-level simulations of non-irradiated and irradiated Low-Gain Avalanche Diode (LGAD) detectors and their validation against experimental data will be presented. Thanks to the intrinsic multiplication of the charge within these silicon sensors, it is possible to improve the signal to noise ratio thus limiting its drastic reduction with fluence, as it happens instead for standard silicon detectors. Therefore, special attention has been devoted to the choice of the avalanche model, which allows the simulation findings to better fit with experimental data. Moreover, a radiation damage model (called "New University of Perugia TCAD model") has been fully implemented within the simulation environment, to have a predictive insight into the electrical behavior and the charge collection properties of the LGAD detectors, up to the highest particle fluences expected in the future High Energy Physics (HEP) experiments. This numerical model allows to consider the comprehensive bulk and surface damage effects induced by radiation on silicon sensors. By coupling the "New University of Perugia TCAD model" with an analytical model that describes the mechanism of acceptor removal in the multiplication layer, it has been possible to reproduce experimental data with high accuracy, demonstrating the reliability of the simulation framework.